Our farmers' market - Meinking, Mary (2020)
"Our farmers' market is a busy place! Lots of community helpers work at the farmers' market. Readers will learn about who works at a farmers' market, what the workers do, and what makes a farmers' market special. Simple, at-level text and vibrant photos help readers learn all about farmers' markets in the community"--
Includes index.
Ages 4-8
Keywords: Farmers' markets -- Juvenile literature